2013
DOI: 10.1108/09526861311319546
|View full text |Cite
|
Sign up to set email alerts
|

Balanced scorecard: application in the General Panarcadian Hospital of Tripolis, Greece

Abstract: Special attention is given to the peculiarities of the Greek public health situation. The paper presents for the first time a real life example of applying BSC in the Greek public health sector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 18 publications
1
32
0
4
Order By: Relevance
“…= 1.147), because they agreed that the benefits of the BSC would outweigh its costs if it were implemented successfully (mean response 2.76, std.= 1.147). These results are in agreement with the studies by Giannopoulos et al (2013), Koumpouros (2013), and Kasasbeh (2018) who stated that the reasons for not applying BSC are a lack of awareness of BSC application and its role in improving performance. The results agree with the studies of Al-Zwyalif (2012), and Cheng, Dainty, and Moore (2007).…”
Section: Obstacles Faced the Bsc Application In The Egyptian Travel Asupporting
confidence: 92%
“…= 1.147), because they agreed that the benefits of the BSC would outweigh its costs if it were implemented successfully (mean response 2.76, std.= 1.147). These results are in agreement with the studies by Giannopoulos et al (2013), Koumpouros (2013), and Kasasbeh (2018) who stated that the reasons for not applying BSC are a lack of awareness of BSC application and its role in improving performance. The results agree with the studies of Al-Zwyalif (2012), and Cheng, Dainty, and Moore (2007).…”
Section: Obstacles Faced the Bsc Application In The Egyptian Travel Asupporting
confidence: 92%
“…Finally, only 1 study evaluated the indicators depending on more than 1 source [41], for example; patient satisfaction was evaluated from the patient's perspective as well as the HCWs'' perspective 3.2.6 BSC generation Resulted studies used different versions of BSC. 1st generation's aspects; explanation and definition of perspectives and indicators, and how to measure each indicator was performed only in 7 papers [30,34,36,37,[40][41][42], and partially in 1 paper where only customer and patient satisfaction were explained with how they were measured [43]. Also, only 5 papers specified the source for each perspective/indicator [30,35,36,41,42], while one mentioned them partially [34].…”
Section: Data Collectionmentioning
confidence: 99%
“…Karra and Papadopoulos (2005)reported that BSC framework provides a roadmap of actions, policies, priorities and resources to achieve mission and strategic goals. BSC also being reported for its usefulness in decision making in highly complex and uncertain environment, and effectively underlying existing problems and identifying opportunities for improvements on time (Inamdar et al, 2002;Koumpouros, 2013;Pink et al, 2001). BSC can be used to balance the demands of internal and external stakeholders.…”
Section: Nationally Accredited Journal -Decree No 21/e/kpt/2018mentioning
confidence: 99%